N‐acetylglutamate synthase deficiency with associated 3‐methylglutaconic aciduria: A case report. Issue 5 (22nd July 2022) - Selvanathan, Arthavan; Demetriou, Kalliope; Lynch, Matthew; Lipke, Michelle; Bursle, Carolyn; Elliott, Aoife; Inwood, Anita; Foyn, Leanne; McWhinney, Brett; Coman, David; McGill, Jim
Abstract: N‐acetylglutamate synthase (NAGS) deficiency is a rare autosomal recessive disorder, which results in the inability to activate the key urea cycle enzyme, carbamoylphosphate synthetase 1 (CPS1). Patients often suffer life‐threatening episodes of hyperammonaemia, both in the neonatal period and also at subsequent times of catabolic stress. Because NAGS generates the cofactor for CPS1, these two disorders are difficult to distinguish biochemically. However, there have now been numerous case reports of 3‐methylglutaconic aciduria (3‐MGA), a marker seen in mitochondrial disorders, occurring in CPS1 deficiency. Previously, this had not been reported in NAGS deficiency. We report a four‐day‐old neonate who was noted to have 3‐MGA at the time of significant hyperammonaemia and lactic acidosis. Low plasma citrulline and borderline orotic aciduria were additional findings that suggested a proximal urea cycle disorder. Subsequent molecular testing identified bi‐allelic pathogenic variants in NAGS . The 3‐MGA was present at the time of persistent lactic acidosis, but improved with normalization of serum lactate, suggesting that it may reflect secondary mitochondrial dysfunction. NAGS deficiency should therefore also be considered in patients with hyperammonaemia and 3‐MGA. Studies in larger numbers of patients are required to determine whether it could be a biomarker for severe decompensations.